Empirical study on the determinants of quality of work life in local government institutions - Kuczaj, Kamila (Management Sciences, 2017)
The relationship between quality of work life (QWL) and particular work aspects has been heavily re-searched over the years. Despite this continuous interest, there is no commonly recognized list of determinants of QWL that has been accepted by the majority of researchers. This study tests ten major job factors, and their relationship with work life quality is presented and discussed. The results are based on quantitative data that was collected via questionnaire. This type of analysis has not previously been conducted in Poland in the public sector. The results, based on a regional probability sample of office workers, help to define the determinants of quality of work life in local government institutions. The results indicate a relatively strong relationship between four of the ten described job aspects and QWL. The paper contains a list of conditions that are conducive to the development of QWL in local government, as well as institutional recommendations
Nauki o Zarządzaniu = Management Sciences, 2017, Nr 4 (33), s. 52-58
Keywords: quality of work life; QWL determinants; public sector; local government; jakość życia w miejscu pracy (QWL); determinanty jakości życia w miejscu pracy; sektor publiczny; samorząd terytorialny